Two Poets, One Poem: An Evaluation on Ghazal(s) of “-sı yoh/-sı yok” Redif Available in Divans of Nesimi and Şeyhi - Kuzu, Fettah (Fırat University, 2023)
Seyyid Nesimi is an artist lived in 14th century and gained appreciation in all times and all Turkish world. Şeyhi on the other hand, is a pioneer poet of classical Turkish poetry, lived in 15th century. Both poets have poems, of which belonging seems debatable, detected in various divan versions and poetry collections. At this point, it is remarkable that one of two ghazel with “-sı yoh” redif attributed to Nesimi and located in edition critique of his Divan, is also available as exactly the same poem in Divan of Şeyhi. Coinciding the lifetimes of two poets with the same time period is also important related to linguistic features of the aforementioned poem by since dispositions dependent upon the era are possible to be similar on a large scale. Moreover, although the poets belong to different regions of Turkish Literature they do not have distinctive differences in the usage of Turkish. In this study, firstly Divans of both poets are to be examined by taking the version differences into consideration to understand whether there are two different poems resembling each other or there is only one poem and if so, evaluations on identifying the poet of poem will be realised.

Seyyid Nesîmî 14. yüzyılda yaşamış, şiirleriyle sadece döneminin ve Azeri sahasının değil tüm zamanların ve tüm Türk dünyasının beğenisini kazanmış büyük bir sanatçıdır. Şeyhî de 15. yüzyıl Anadolu sahasında yetişmiş Klasik Türk edebiyatının önemli şairlerindendir. Her iki şairin de farklı dîvân nüshalarında ve muhtelif şiir mecmualarında tespit edilen ancak onlara aidiyeti tartışmalı olan şiirleri mevcuttur. Bu noktada Nesîmî’ye nispet edilen ve Dîvânı’nın tenkitli metninde yer alan “sı yoh” redifli iki gazelden birinin, kendisiyle çağdaş sayılabilecek Şeyhî’nin Dîvânı’nda da neredeyse birebir aynı olarak bulunması dikkat çekici bir mahiyet arz etmektedir. İki şairin yaşadıkları dönemin yaklaşık olarak aynı zaman dilimine rastlaması, özellikle söz konusu şiirin dil malzemesi noktasında döneme bağlı tasarrufların büyük ölçüde aynı olabileceği ihtimaliyle önem arz etmektedir. Ayrıca her ne kadar şairler farklı iki edebî sahanın sanatçıları olsa da bu iki edebî saha Türkçenin kullanımı noktasında ciddi anlamda ayırt edici farklılıklar taşımamaktadır. Bu çalışmada, ilk olarak her iki şairin Dîvânları, nüsha farklılıkları da göz önünde bulundurularak incelenmek suretiyle ortada tek bir şiirin mi yoksa birbirine benzer iki şiirin mi olduğu üzerinde durulacak sonrasında tek bir şiir söz konusuysa kime ait olduğu ile ilgili değerlendirmelere yer verilecektir.
İKİ ŞAİR, BİR ŞİİR: NESÎMÎ VE ŞEYHÎ DÎVÂNLARINDA YER ALAN “-SI YOH/-SI YOK” REDİFLİ GAZEL(LER) ÜZERİNE BİR DEĞERLENDİRME
Keywords: Turkish Islamic Literature; Türk İslam Edebiyatı